Improving the use of lichens as biomonitors of atmospheric metal pollution. (The Science of the total environment, 1999)
The data reported on this study supported the hypothesis that the absence of the lichen Ramalina fastigiata near a copper mine site located on the south of Portugal was related to toxic levels of Cu-dust near the centre of the mine. Lichen biodiversity reflected the impact of the copper-mine dust emissions which were more widespread towards the east, correlated with wind direction and frequency. The chemical analysis of R. fastigiata collected at different distances and in different directions from the mine showed that Cu, K and Mg were derived from the centre of the mine site, confirming thus as the major source of atmospheric dust. Total inhibition of PSII photochemical reactions occurred in R. fastigiata both under field and controlled conditions, when intracellular Cu concentrations exceeded a threshold of approximately 2.0 mumol g-1. No samples of this species were found under field conditions beyond the Cu threshold. Thus, the fluorescence parameter Fv/Fm proved to be a good estimator of the survival capacity of R. fastigiata under field conditions and thus a useful parameter in determining the sensitivity of the lichens (photobiont) to Cu pollution. The intracellular location of Cu allowed an explanation of the physiological changes and the survival of the species in the surroundings of the copper-mine.